Probiotic and Rice-Derived Compound Combination Mitigates Colitis Severity - Ashraf Khalifa; Mayyadah Abdullah Alkuwayti; Basem M. Abdallah; Enas M. Ali; Hairul Islam M. Ibrahim (MDPI AG, 2024)
Background: This study investigated the ability of Enterococcus lactis (E. lactis) and Hasawi rice protein lysate (HPL) to suppress colitis induced by dextran sulfate sodium (DSS) in miceColitis is characterized by inflammation of the colon, and exploring potential therapeutic agents could lead to improved management strategies. Methods: Male mice were subjected to DSS treatment to induce colitis, followed by supplementation with E. lactis and/or HPL. The study assessed various parameters, including disease activity index (DAI) scores, gut permeability measured using FITC-dextran, and superoxide dismutase (SOD) activity in excised colon tissues from both treated and untreated control groups. Results: E. lactis supplementation significantly alleviated DSS-induced colitis, as evidenced by improved DAI scores and enhanced gut permeability. Notably, E. lactis combined with HPL (0.1 mg/108) exhibited superior tolerance to a 0.5% pancreatin solution compared to E. lactis alone. Both E. lactis and the combination treatment significantly increased SOD activity (5.6 ± 0.23 SOD U/mg protein for E. lactis and 6.7 ± 0.23 SOD U/mg protein for the combination) relative to the Azoxymethane (AOM)/DSS group, suggesting a reduction in oxidative stress. Additionally, pro-inflammatory markers were significantly reduced in the group receiving both E. lactis and HPL compared to the E. lactis-only group. Levels of proteins associated with cell death, such as PCNA, PTEN, VEGF, COX-2, and STAT-3, were significantly decreased by 14.8% to 80% following E. lactis supplementation, with the combination treatment showing the most pronounced effects. Conclusions: These findings suggest E. lactis supplementation may be beneficial for colitis, with HPL potential to enhance its effectiveness.